Influence of thinning and foliar fertilization of "Pon Kan" tangerine trees (Citrus reticulata blanco) on the quality of the fruits - Marinho, Cláudia Sales; Souto, Rosilene Ferreira; Sobrinho, Fausto de Souza (Pesquisa Agropecuaria Brasileira, 1993)
On eight-year old 'Pon Kan' tangerine trees distinct levels of thinning (9, 7, 5, 3 and 1 fruit/branch) combined with foliar fertilization (0 and 4 applications) of chelated macro and micronutrients was assessed at the "Escola Superior de Agricultura de Lavras (ESAL), in Lavras, MG, Brazil. The statistical design was in randomized blocks in a factorial scheme, with six replications, and the experimental plots consisted of one branch with nine fruits. The foliar fertilization with commercial fertilizer containing N, Mg, S, B, Mn and Zn was carried out at 12-day intervals since February 1991. The manual thinning increased the fruit weight and diameter and the volume of juice. The foliar fertilization increased statisticaly the fruit weight but not the fruit diameter nor the volume of juice.